1990
DOI: 10.1111/j.1476-5381.1990.tb14669.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of capsaicin on responses of the rabbit ear artery to field stimulation

Abstract: 1 The effects of capsaicin (Cap) on contractions of ring segments of rabbit ear artery induced by field stimulation were studied.2 At low concentrations (0.3-3 gM) Cap caused transient enhancement and at higher concentrations (above 3 pM) inhibition of stimulation-induced contractions, without affecting noradrenaline (NA)-induced contractions. 3 In the continuous presence of high concentrations of Cap, rebound facilitation was observed after inhibition, and at this stage, Cap elicited less inhibition of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…amplitude indicates that this agent enhances purinergic neuromuscular transmission. There are previous reports that capsaicin increases sympathetic nerve‐evoked contractions of mouse and rat vas deferens and rabbit ear artery ( Moritoki et al , 1987 ; 1990; Parlani et al , 1995 ). In mouse vas deferens, in the presence of CGRP 8–37 , capsaicin produced a transient increase in the motor response evoked by sympathetic nerve stimulation that is blocked by the tachykinin receptor antagonist, CP96,347 ( Parlani et al , 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…amplitude indicates that this agent enhances purinergic neuromuscular transmission. There are previous reports that capsaicin increases sympathetic nerve‐evoked contractions of mouse and rat vas deferens and rabbit ear artery ( Moritoki et al , 1987 ; 1990; Parlani et al , 1995 ). In mouse vas deferens, in the presence of CGRP 8–37 , capsaicin produced a transient increase in the motor response evoked by sympathetic nerve stimulation that is blocked by the tachykinin receptor antagonist, CP96,347 ( Parlani et al , 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the facilitatory effect of capsaicin in both rat vas deferens ( Moritoki et al , 1987 ) and rabbit ear artery ( Moritoki et al , 1990 ) does not desensitize, questioning whether its actions in these tissues are mediated through the excitation of the primary afferent axons. In rabbit ear artery, low concentrations of capsaicin increased sympathetic nerve‐evoked contractions, whereas higher concentrations were inhibitory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also showed involvement of PGs in the cytoprotective action of capsaicin against ethanol (9,10) or in the capsaicin-induced gastric hyperemic re sponse (11). However, the relation of capsaicin to PG generation is not without controversy; capsaicin may enhance the formation of PGs in vascular tissues of rab bits (19), while no effect on PG generation is observed in the rat gastric mucosa and other tissues (2,20). In domethacin has several other effects that are unrelated to PGs (21,22), and these actions might be associated with suppression of the HC03 response to capsaicin.…”
Section: Discussionmentioning
confidence: 99%
“…However, its specificity for afferent neurons is not absolute, and some of the acute effects of the drug on blood vessels appear to result from a direct action on vascular muscle (Donnerer and Lembeck 1982;Duckles 1986;B6ny et al 1989;Edvinsson et al 1990; Moritoki et al 1990) and endothelium (Kenins et al 1984). The label "capsaicin sensitive" is applied to those afferent neurons which acutely are excited and in the long term are damaged by the drug.…”
Section: Capsaicin-sensitive Neuronsmentioning
confidence: 99%